Comparison of complications in abdominal hysterectomy versus vaginal hysterectomy - N Asnafi; K Hajian; A Abdollahi (JRI, 2004)
Introduction: Hysterectomy is one of the most common operations in the world. It is divided into two main abdominal and vaginal categories. Each type has usually specific indications but sometimes they have common indications. The main causes of abdominal hysterectomy are uterine fibroma, AUB, resistant PID, endometriosis, gynecologic malignancies, adenomyosis with vaginal bleeding, pelvic pain and cervical CIN and the most important indication for vaginal hysterectomy is uterine prolaps. Considering the importance and prevalence of hysterectomy and its side effects, we decided to compare the complications of vaginal versus abdominal hysteric-tomy to try to define more solid criteria for selecting hysterectomy method for the candidate patients. Materials and Methods: This is a case-control (retrospective) analytic study.Data was collected from March 2001 until March 2003 of patient who had hysterectomies in GYN Department of Yahyanejad hospital in Babol. Of the 339 women who had undergone hysterectomy, 57 (16.8%) had received vaginal and 282 (83.2%) abdominal hysterectomy. The Variables Considered included age, days of hospitalization, decrease in hemoglobin concentration and other early side effects of hysterectomy. The data was analyzed by SPSS software Program using 2, t- test and fisher's exact test and multiple logistic model. Results: The mean age of the Patients who had undergone hysterectomy was 58.512 years for Vaginal and 44.697.9 years for abdominal hysterectomy. The overall Complication rates were 23.7% and 5.3% (p=0.01) for abdominal and Vaginal hysterectomies, respectively. Fever was the main complication after surgery with a frequency of 18.4% and 3.5% for abdominal and vaginal hysterectomies, respectively. The decrease in hematocrit was lower in abdominal (2.392.05%) than in vaginal (3.761.32%) hysterectomy (p<0.001). Conclusion: The results indicate that the overall complications in vaginal hysterectomy are less than abdominal which may suggest that vaginal hysterectomy may be an appropriate alternative for abdominal hysterectomy.
Keywords: Hysterectomy, Abdominal hysterectomy, Vaginal hysterectomy, Uterine fibroma, Abenomyosis